Interactive Multimedia Design Based on Discovery Learning With Google Sites on Parabolic Motion Material to Improve Students' Critical Thinking Ability - Rizal, Fitriyani; Festiyed, Festiyed; Mufit, Fatni; Suherman, Dea Stivani (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
The advancement of technology in line with the demands of 21st-century learning presents a new perspective. Students are encouraged to develop critical thinking skills. According to the findings from this study, students exhibit low critical thinking abilities, and learning remains teacher-centered. To address this issue, the solution proposed is the creation of interactive multimedia. The research aims to produce, validate, and assess the practicality of this interactive multimedia. The design of the interactive multimedia follows the Dick & Carey learning design model. Based on the research results, an interactive multimedia resource was developed featuring six syntax elements of discovery learning, aimed at enhancing students' critical thinking skills related to the topic of parabolic motion, created using Google Sites. The validation results indicated a very high validity, with a Cohen's kappa value of 0.80, categorized as valid. Additionally, the practicality test results demonstrated a value of 0.83, indicating that the multimedia is very practical. Thus, it can be concluded that the interactive multimedia based on discovery learning, supported by Google Sites, for the material on parabolic motion, is valid and practical for improving high school students' critical thinking abilities.